All-solid waste cementing material and preparation method thereof
By adding interface regulators during grinding, the problems of low activity and low grinding efficiency of all solid waste gelling materials are solved, and the mechanical properties and durability of the materials are significantly improved, and the feasibility of large-scale industrial production is achieved.
Patent Information
- Application Number
- CN202510061046.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-15
AI Technical Summary
The existing all-solid waste gelling materials have low activity, difficulty in pretreatment, and low grinding efficiency, making it difficult to meet the design mechanical strength and stability and durability requirements.
The interface regulator is added during the grinding process. By reducing the surface energy of the powder particles, the particles are prevented from agglomeration, the fluidity of the powder is improved, the particles are easier to crush, the reaction activity inside the solid waste gelling material is stimulated, and the fluidity and grinding efficiency of the grinding powder are improved.
It significantly improves the activity index, compressive strength and flexural strength of solid waste-based gelling materials, reduces the power consumption of the mill, improves the grinding efficiency, and achieves the high strength and durability of the material.
Smart Images

Figure BDA0005242899880000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to an all-solid waste gelling material and a preparation method thereof. Background Art
[0002] With the accelerated development of industrialization, the amount of industrial solid waste such as red mud, steel slag, and fly ash has continued to increase, occupying a large amount of arable land, and the heavy metal ions they contain have caused serious pollution to the environment. At present, the utilization of industrial solid waste is mainly used as filling cementitious materials. The cost of ordinary silicate cement is too high. Relevant workers have been constantly trying to use solid waste to replace cement to reduce material costs. However, due to the various characteristics of solid waste, such as low hydration activity and volume stability, it is difficult for filling materials prepared by using large amounts of solid waste to replace cement to meet the design requirements of mechanical strength and stability and durability.
[0003] Solid waste-based cementitious materials are mostly composed of non-clinker base materials and active stimulants. Currently, cementitious materials prepared from all solid waste have low activity and the pretreatment of raw materials is difficult. Mechanical activation measures such as grinding are usually used to improve the activity of cementitious materials, but the effect is minimal.
[0004] Chinese patent document CN111499228A discloses a cementitious material for mortar and its use, including: pre-treatment of steel slag particles, the particle fineness of which is 0.35mm and the residue is less than 3%; subjecting the pre-treated steel slag particles to mechanical pulses to obtain steel slag powder, the particle size distribution of which is as follows: ≤15μm accounts for 5-35%, ≤45μm accounts for 40-75%, and ≤60μm accounts for 92-97%; and, mixing the steel slag powder with blast furnace slag powder and gypsum to obtain a cementitious material. The cementitious material prepared by the invention has a fast early hydration reaction, high strength, low self-shrinkage rate, strong volume stability, and excellent anti-cracking performance and anti-freeze-thaw performance; it can have high dosage, small slump, good pumping performance and purification capacity; it is used to replace silicate cement in mortar to reduce cement usage and production costs. This patent prepares cementitious materials by pre-doping steel slag and then mixing and grinding it. After the pre-doping treatment, it needs to undergo mechanical pulses, which places high demands on equipment, increases production costs, and is not suitable for large-scale industrial production. Summary of the invention
[0005] The main purpose of the present invention is to propose a solid waste gelling material suitable for large-scale industrial production and a preparation method thereof. By adding an interface regulator during the grinding process, the particles can be prevented from agglomerating, the fluidity of the powder can be improved, the particles can be made easier to crush, the reaction activity inside the solid waste gelling material can be better stimulated, the fluidity of the ground powder can be improved, thereby reducing the power consumption of the mill, improving the grinding efficiency, and better stimulating the reaction activity inside the solid waste gelling material.
[0006] To achieve the above-mentioned purpose, the present invention proposes an all-solid waste cementitious material, characterized in that it comprises the following components in parts by weight: 30-45 parts of steel slag, 20-30 parts of slag, 10-20 parts of red mud, 20-25 parts of carbide slag, 10-20 parts of fly ash, 5-10 parts of interface regulator, and 5-20 parts of gypsum.
[0007] Preferably, the slag is a by-product of blast furnace ironmaking.
[0008] Preferably, the fly ash is Class II fly ash.
[0009] Preferably, the preparation method of the interface regulator is as follows:
[0010] Molybdenum disulfide is added to an ethanol aqueous solution, KH550 is added, the reaction is heated, filtered, the solid is collected, washed, dried, and dispersed in chloroform, tiglic acid and EDC / NHS aqueous solution are added, the pH value is adjusted to weak acidity, the reaction is heated, filtered, the solid is collected, washed, dried, and added to N, N-dimethylformamide, azobisisobutyronitrile is added, acryloyloxyethyltrimethylammonium chloride is added dropwise under heating conditions, the reaction is kept warm after the addition is completed, the reaction is cooled and filtered after completion, the solid is collected, washed, and dried to obtain the interface regulator.
[0011] Preferably, the mass ratio of molybdenum disulfide, KH550, tiglic acid, and acryloyloxyethyltrimethylammonium chloride is 15-25:2-3:10-13:6-8.
[0012] Preferably, the concentration of EDC in the EDC / NHS aqueous solution is 30-40 mM / L, and the concentration of NHS is 40-50 mM / L.
[0013] The interface regulator of the present invention can significantly reduce the surface energy of powder particles, prevent particle agglomeration, improve the fluidity of powder, make particles easier to crush, better stimulate the reaction activity inside solid waste gelling materials to improve the fluidity of ground powder, thereby reducing mill power consumption and improving grinding efficiency, better stimulate the reaction activity inside solid waste gelling materials, promote material hydration reaction, generate more hydration products, and thus improve the strength and durability of the material.
[0014] Preferably, the gypsum is at least one of anhydrite, fluorite, phosphogypsum and desulfurized gypsum.
[0015] Further preferably, the gypsum is desulfurized gypsum.
[0016] The present invention also provides a method for preparing the all-solid waste gelling material, comprising the following steps:
[0017] The steel slag, carbide slag and gypsum are mixed, crushed and sieved, and then an interface regulator is added to perform a first grinding to obtain a first mixture; slag, red mud and an interface regulator are mixed and then performed a second grinding to obtain a second mixture; fly ash, the first mixture and the second mixture are mixed and stirred to obtain the all-solid waste cementitious material.
[0018] Preferably, the particle size of the steel slag, carbide slag and gypsum after crushing is 2-10 mm.
[0019] Preferably, the surface area of the first mixture is 700-800m 2 / kg; the surface area of the second mixture is 650-750m 2 / kg.
[0020] The present invention makes full use of various industrial solid wastes such as steel slag, red mud, carbide slag, fly ash, slag, gypsum, etc., to realize the recycling of resources. These solid wastes can generate hydration products, form a dense network structure, provide strength, and realize the harmless treatment and resource utilization of solid waste. As a substitute for cement, it has good economic and environmental benefits, achieves the goal of carbon reduction in the field of cementitious materials, and meets the current energy conservation, environmental protection, and circular economy industrial development requirements; the first mixture obtained by grinding steel slag, carbide slag, and gypsum is mixed with the second mixture obtained by grinding slag and red mud, so that it can better play its role of filling and improving the aggregate interface, thereby significantly improving the activity index as well as the compressive strength and flexural strength of the solid waste-based cementitious material.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) In the all-solid waste gelling material of the present invention, the high content of alkaline components in steel slag and red mud can provide an alkaline hydration environment for the system, stimulate the condensation of slag to form CSH gel, which can effectively fill and connect pores and improve the strength and density of the material. The fly ash has high reactivity inside. Under alkaline conditions, its inert coating layer is destroyed, so it has volcanic ash activity and can participate in the hydration reaction to generate hydration products such as CASH / CSH, thereby improving the strength and durability of the material. Gypsum contains a large amount of sulfate ions, which can promote the reaction of slag with Al in red mud under alkaline conditions. 3+ and Si 4+ Ions dissolve out, promoting the formation of more hydration products, and sulfate can further react with hydration products to form ettringite, forming a dense network structure, providing strength, and achieving harmless treatment and resource utilization of solid waste;
[0023] (2) The present invention adds an interface regulator during the grinding process. The preparation of the interface regulator is to first introduce an amino group into the lubricant molybdenum disulfide, and then react with tiglic acid to generate amidated molybdenum disulfide. The carbon-carbon double bond on the tiglic acid molecule can react with positively charged acryloyloxyethyl trimethyl ammonium chloride to graft acryloyloxyethyl trimethyl ammonium chloride onto the molybdenum disulfide. The molybdenum disulfide can effectively reduce the friction resistance between the powder particles, reduce wear, and improve the grinding efficiency. By amidating it, the amide group can adsorb heavy metal ions in the solid waste powder, which is beneficial to improving the mechanical properties of the material. By introducing positively charged acryloyloxyethyl trimethyl ammonium chloride on its surface, the interface regulator is adsorbed on the surface of the powder particles and in new and old cracks through the charge during the grinding process, so that the powder particles are hindered from approaching each other during the grinding process, and the particles are prevented from agglomerating. The particles are easier to crush, and the reaction activity inside the solid waste gel material can be better stimulated, the material hydration reaction is promoted, and more hydration products are generated, thereby improving the strength and durability of the material. DETAILED DESCRIPTION
[0024] To avoid redundancy, the items used in the following examples are all commercially available products unless otherwise specified, and the methods used are all conventional methods unless otherwise specified.
[0025] The sources of some raw materials used in the present invention are as follows:
[0026] Steel slag was purchased from Shijiazhuang Zenghua New Material Technology Co., Ltd., and its chemical composition is CaO content of 42.3%, Fe 2 O 3 The content is 22.9%, SiO 2 The content is 15.2%, MgO content is 7.1%, Al 2 O 3 The content is 5.3%, and the content of other substances is 7.2%.
[0027] Slag, from Yongfeng Steel Co., Ltd., has a chemical composition of Al 2 O 3 The content is 15.26%, SiO 2 The content is 35.26%, Fe 2 O 3 The content is 0.81%, SO 3 The content is 1.27%, K 2 O content is 0.43%, CaO content is 36.03%, Na 2 The O content is 0.10%, and the content of other substances is 10.84%.
[0028] Red mud, sintered red mud, comes from Wanfang Aluminum Co., Ltd., Jiaozuo, Henan Province, and its chemical composition is SiO 2The content is 18.43%, Al 2 O 3 The content is 7.36%, Fe 2 O 3 The content is 7.04%, TiO 2 The content is 2.77%, the CaO content is 36.46%, and the SO 3 The content is 2.05%, Na 2 The O content is 2.56%, the content of other substances is 1.68%, and the loss on ignition is 20.43%.
[0029] Calcium carbide slag, from Xingtai Fuyuan Acetylene Plant, has a chemical composition of 67.95% CaO, 67.95% SiO 2 The content is 4.99%, Al 2 O 3 The content is 2.344%, Fe 2 O 3 The content is 0.48%, the MgO content is 0.24%, and the SO 3 The content is 0.2% and the loss on ignition is 23.57%.
[0030] Fly ash, grade II, from Wuhan Huadian Industrial Co., Ltd. Fly Ash Development Company, its chemical composition is Al 2 O 3 The content is 37.45%, SiO 2 The content is 32.27%, Fe 2 O 3 The content is 20.7%, TiO 2 The content is 3.9%, CaO content is 2.4%, SO 3 The content is 0.6%, the content of MgO is 0.45%, and the content of other substances is 0.23%.
[0031] Molybdenum disulfide, 500 mesh, was purchased from Hebei Teng Bimetallic Materials Co., Ltd.
[0032] Gypsum, desulfurized gypsum, 200 mesh, was purchased from Hebei Henghe Mineral Products Co., Ltd.
[0033] Example 1
[0034] A method for preparing a solid waste cementitious material comprises the following steps:
[0035] 400g of steel slag, 220g of carbide slag and 100g of desulfurized gypsum were mixed and crushed to a particle size of 2-10mm. After screening, 30g of interface regulator was added for the first grinding to obtain a surface area of 700-800m 2 / kg of the first mixture; 250g of slag, 150g of red mud, and 30g of interface regulator were mixed and ground for the second time to obtain 650-750m2 / kg second mixture; 168g fly ash, the first mixture and the second mixture are mixed and stirred evenly to obtain the all-solid waste cementitious material.
[0036] The preparation method of the interface regulator comprises the following steps:
[0037] 21.5 g of molybdenum disulfide was added to 200 mL of 50 wt% ethanol aqueous solution, 2.56 g of KH550 was added, and the mixture was heated at 60° C. for 2 h. After the reaction was completed, the mixture was cooled and filtered. After the solid was collected, it was washed and dried, and then dispersed in 200 mL of chloroform. 11.6 g of tiglic acid and 160 mL of EDC / NHS aqueous solution were added. The concentration of EDC in the EDC / NHS aqueous solution was 35 mM / L, and the concentration of NHS was 45 mM / L. The pH value was adjusted to 6, and the mixture was heated at 60° C. for 6 h. After the reaction was completed, the mixture was cooled and filtered. After the solid was collected, it was washed and dried, and then added to 200 mL of N,N-dimethylformamide. 0.3 g of azobisisobutyronitrile was added, and the mixture was heated to 70° C. 7.2 g of acryloyloxyethyltrimethylammonium chloride was added dropwise. After the addition was completed, the mixture was kept warm for 3 h. After the reaction was completed, the mixture was cooled and filtered. After the solid was collected, it was washed and dried to obtain the interface regulator.
[0038] Example 2
[0039] A method for preparing a solid waste cementitious material comprises the following steps:
[0040] 300g of steel slag, 200g of carbide slag and 50g of desulfurized gypsum were mixed and crushed to a particle size of 2-10mm. After screening, 25g of interface regulator was added for the first grinding to obtain a surface area of 700-800m 2 / kg of the first mixture; 200g of slag, 100g of red mud, and 25g of interface regulator were mixed and ground for the second time to obtain 650-750m 2 / kg second mixture; 100g fly ash, the first mixture and the second mixture are mixed and stirred evenly to obtain the all-solid waste cementitious material.
[0041] The preparation method of the interface regulator comprises the following steps:
[0042] 15g of molybdenum disulfide is added to 200mL of 50wt% ethanol aqueous solution, 2g of KH550 is added, the mixture is heated at 60°C for 2h, filtered, the solid is collected, washed, dried, and dispersed in 200mL of chloroform, 10g of tiglic acid and 150mL of EDC / NHS aqueous solution are added, the concentration of EDC in the EDC / NHS aqueous solution is 30mM / L, and the concentration of NHS is 40mM / L; the pH value is adjusted to 6, the mixture is heated at 60°C for 6h, cooled and filtered after the reaction is completed, the solid is collected, washed, dried, and added to 200mL of N,N-dimethylformamide, 0.25g of azobisisobutyronitrile and 6g of acryloyloxyethyltrimethylammonium chloride are added under heating conditions, the mixture is heated for 3h after the addition is completed, cooled and filtered after the reaction is completed, the solid is collected, washed, and dried to obtain the interface regulator.
[0043] Example 3
[0044] A method for preparing a solid waste cementitious material comprises the following steps:
[0045] 450g of steel slag, 250g of carbide slag and 200g of desulfurized gypsum were mixed and crushed to a particle size of 2-10mm. After screening, 50g of interface regulator was added for the first grinding to obtain a surface area of 700-800m 2 / kg of the first mixture; 300g of slag, 200g of red mud, 50g of interface regulator were mixed and ground for the second time to obtain 650-750m 2 / kg second mixture; 200g fly ash, the first mixture and the second mixture are mixed and stirred evenly to obtain the all-solid waste cementitious material.
[0046] The preparation method of the interface regulator comprises the following steps:
[0047] 25g of molybdenum disulfide is added to 200mL of 50wt% ethanol aqueous solution, 3g of KH550 is added, and the mixture is heated at 60°C for 2h. After the reaction is completed, the mixture is cooled and filtered, and the solid is collected, washed, dried, and dispersed in 200mL of chloroform. 13g of tiglic acid and 180mL of EDC / NHS aqueous solution are added, and the concentration of EDC in the EDC / NHS aqueous solution is 40mM / L, and the concentration of NHS is 50mM / L. The pH value is adjusted to 6, and the mixture is heated at 60°C for 6h. After the reaction is completed, the mixture is cooled and filtered, and the solid is collected, washed, dried, and added to 200mL of N,N-dimethylformamide. 0.4g of azobisisobutyronitrile and 8g of acryloyloxyethyltrimethylammonium chloride are added under heating conditions. After the addition is completed, the mixture is kept warm for 3h. After the reaction is completed, the mixture is cooled and filtered, and the solid is collected, washed, and dried to obtain the interface regulator.
[0048] Comparative Example 1
[0049] A method for preparing a solid waste cementitious material is similar to Example 1, except that acryloyloxyethyl trimethyl ammonium chloride is not added in the preparation method of the interface regulator, and specifically comprises the following steps:
[0050] 400g of steel slag, 220g of carbide slag and 100g of desulfurized gypsum are mixed and crushed to a particle size of 2-10mm. After screening, 30g of interface regulator is added and the first grinding is performed to obtain a first mixture; 250g of slag, 150g of red mud and 30g of interface regulator are mixed and the second grinding is performed to obtain a second mixture; 168g of fly ash, the first mixture and the second mixture are mixed and stirred to obtain the all-solid waste cementitious material.
[0051] The preparation method of the interface regulator comprises the following steps:
[0052] 21.5 g of molybdenum disulfide was added to 200 mL of 50 wt% ethanol aqueous solution, and 2.56 g of KH550 was added. The mixture was heated at 60° C. for 2 h. After the reaction was completed, the mixture was cooled and filtered. After the solid was collected, it was washed and dried, and then dispersed in 200 mL of chloroform. 11.6 g of tiglic acid and 160 mL of EDC / NHS aqueous solution were added. The concentration of EDC in the EDC / NHS aqueous solution was 35 mM / L, and the concentration of NHS was 45 mM / L. The pH value was adjusted to 6, and the mixture was heated at 60° C. for 6 h. After the reaction was completed, the mixture was cooled and filtered. After the solid was collected, it was washed and dried, and the interface regulator was obtained.
[0053] Comparative Example 2
[0054] A method for preparing a solid waste cementitious material is similar to Example 1, except that the interface regulator is a mixture of molybdenum disulfide and acryloyloxyethyl trimethylammonium chloride, and specifically comprises the following steps:
[0055] 400g of steel slag, 220g of carbide slag and 100g of desulfurized gypsum are mixed and crushed to a particle size of 2-10mm. After screening, 22.5g of molybdenum disulfide and 7.5g of acryloyloxyethyltrimethylammonium chloride are added and mixed, and then the mixture is ground for the first time to obtain a first mixture; 250g of slag, 150g of red mud, 30g 22.5g of molybdenum disulfide and 7.5g of acryloyloxyethyltrimethylammonium chloride are mixed and ground for the second time to obtain a second mixture; 168g of fly ash, the first mixture and the second mixture are mixed and stirred to obtain the all-solid waste cementitious material.
[0056] Comparative Example 3
[0057] A method for preparing a solid waste cementitious material is similar to Example 1, except that the interface regulator is molybdenum disulfide, and specifically comprises the following steps:
[0058] 400g of steel slag, 220g of carbide slag and 100g of desulfurized gypsum are mixed and crushed to a particle size of 2-10mm. After screening, 30g of interface regulator is added and the first grinding is performed to obtain a first mixture; 250g of slag, 150g of red mud and 30g of interface regulator are mixed and the second grinding is performed to obtain a second mixture; 168g of fly ash, the first mixture and the second mixture are mixed and stirred to obtain the all-solid waste cementitious material.
[0059] Performance Testing
[0060] Activity index: The 7d activity index of the all-solid waste cementitious materials prepared in Examples 1-3 and Comparative Examples 1-3 was determined by referring to the slag powder activity index method in Appendix A of GB / T18046-2017 Granulated blast furnace slag powder for cement, mortar and concrete. The test results are shown in Table 1:
[0061] Table 1 Activity index test results of all-solid waste cementitious materials
[0062] Activity index (%) Example 1 125 Example 2 126 Example 3 123 Comparative Example 1 76 Comparative Example 2 68 Comparative Example 3 52
[0063] Mechanical properties test: The all-solid waste cementitious materials obtained in Examples 1-3 and Comparative Examples 1-3 were prepared into mortar test blocks at a water-cement ratio of 0.32. The mortar mixing process was made according to GB / T17671-2021 "Test Method for Cement Mortar Strength", and a standard test piece of 40mm×40mm×160mm was made. The mortar was cured under standard curing conditions to the corresponding age, and the compressive and flexural strength of the mortar was tested. The test results are shown in Table 2:
[0064] Table 2 Mechanical properties test of all-solid waste cementitious materials
[0065]
[0066] It can be seen from the experimental data in Table 1 and Table 2 that the all-solid waste cementitious material prepared by the present invention has good potential activity, and has good compressive strength and flexural strength.
[0067] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.
Claims
1. A solid waste cementitious material, characterized in that: The invention comprises the following components in parts by weight: 30-45 parts of steel slag, 20-30 parts of slag, 10-20 parts of red mud, 20-25 parts of carbide slag, 10-20 parts of fly ash, 5-10 parts of interface regulator and 5-20 parts of gypsum.
2. The all-solid waste gelling material according to claim 1, characterized in that: The fly ash is Class II fly ash.
3. The all-solid waste cementitious material according to claim 1, characterized in that: The preparation method of the interface regulator is as follows: Molybdenum disulfide is added to an ethanol aqueous solution, KH550 is added, the reaction is heated, filtered, the solid is collected, washed, dried, and dispersed in chloroform, tiglic acid and EDC / NHS aqueous solution are added, the pH value is adjusted to weak acidity, the reaction is heated, filtered, the solid is collected, washed, dried, and added to N, N-dimethylformamide, azobisisobutyronitrile is added, acryloyloxyethyltrimethylammonium chloride is added dropwise under heating conditions, the reaction is kept warm after the addition is completed, the reaction is cooled and filtered after completion, the solid is collected, washed, and dried to obtain the interface regulator.
4. The all-solid waste cementitious material according to claim 3, characterized in that: The mass ratio of the molybdenum disulfide, KH550, tiglic acid and acryloyloxyethyltrimethylammonium chloride is 15-25:2-3:10-13:6-8.
5. The all-solid waste gelling material according to claim 3, characterized in that: The concentration of EDC in the EDC / NHS aqueous solution is 30-40 mM / L, and the concentration of NHS is 40-50 mM / L.
6. The all-solid waste cementitious material according to claim 1, characterized in that: The gypsum is at least one of anhydrite, fluorite, phosphogypsum and desulfurized gypsum.
7. The all-solid waste gelling material according to claim 6, characterized in that: The gypsum is desulfurized gypsum.
8. A method for preparing the all-solid waste gelling material according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: mixing steel slag, carbide slag and gypsum, crushing and screening them, and then adding an interface regulator to perform a first grinding to obtain a first mixture; mixing slag, red mud and an interface regulator and performing a second grinding to obtain a second mixture; and mixing and stirring fly ash, the first mixture and the second mixture to obtain the all-solid waste cementitious material.
9. The preparation method according to claim 8, characterized in that: The particle size of the steel slag, carbide slag and gypsum after crushing is 2-10mm.
10. The preparation method according to claim 8, characterized in that: Preferably, the surface area of the first mixture is 700-800m 2 / kg; the surface area of the second mixture is 650-750m 2 / kg.
Citation Information
Patent Citations
Cementing material for mortar and application thereof
CN111499228A
Ecological cementing material and preparation method thereof
CN114394772A
All-solid-waste clinker-free cementing material, conductive mortar and preparation method of all-solid-waste clinker-free cementing material
CN114671633A
Preparation method of solid-waste-based superfine special composite cementing material and cementing material
CN115893879A
Method for preparing cemented filling material through cooperation of multi-source industrial waste residues and superfine tailings
CN116639945A
Cited By
Multi-source solid waste-based cementing material and preparation method thereof
CN120554009A
All-solid waste negative carbon cementing material as well as preparation method and application thereof
CN120923161A